2018
DOI: 10.1080/07317115.2018.1442380
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Experiences with Audiovisual Virtual Reality: Perceived Usefulness and Other Factors Influencing Technology Acceptance

Abstract: As older adults are interested in using VR, especially if poor health prevents the continuation of desirable activities or new experiences, it is important to respond to older adults' preferences and remove barriers that limit use and enjoyment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 15 publications
9
107
0
4
Order By: Relevance
“…The results from the debriefing questionnaire were positive and in agreement with previous research, finding acceptance of using HMDs in older adults [ 46 - 48 ]. This study further expands the knowledge of acceptability by demonstrating that VR using HMDs can be used to deliver reminiscence therapy with participants of varying levels of cognitive impairment, including minimal, mild, and moderate impairment, as assessed by the PAS.…”
Section: Discussionsupporting
confidence: 89%
“…The results from the debriefing questionnaire were positive and in agreement with previous research, finding acceptance of using HMDs in older adults [ 46 - 48 ]. This study further expands the knowledge of acceptability by demonstrating that VR using HMDs can be used to deliver reminiscence therapy with participants of varying levels of cognitive impairment, including minimal, mild, and moderate impairment, as assessed by the PAS.…”
Section: Discussionsupporting
confidence: 89%
“…The results from the debriefing questionnaire were positive and in agreeance with previous research finding acceptance of using HMDs in older adults (Huygelier et al, 2019;Roberts et al, 2019;Rose et al, 2019). This study further expands the knowledge of acceptability by demonstrating that VR using HMDs can be used to deliver reminiscence therapy with participants of varying levels of cognitive impairment including minimal, mild and moderate as assessed by the PAS.…”
Section: Discussionsupporting
confidence: 87%
“…Recent research has found that older adults, including those with cognitive decline can tolerate using HMDs and have reported positive experiences (Brimelow, Dawe, & Dissanayaka, 2019;Huygelier, Schraepen, van Ee, Vanden Abeele, & Gillebert, 2019;Roberts, De Schutter, Franks, & Radina, 2019;Rose et al, 2019). There has also been success with using HMDs for memory training in older adults with significant improvements in memory tests (d=.7) compared with a control group receiving music therapy (Optale et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Roberts et al also certified that usefulness was a key factor influencing the acceptance of VR by the elderly, and suggested that increasing interactivity could maximize the advantages of VR to promote social interaction with family and friends. The expected categories include travel, continued education, reminiscence, and self-care [28]. In addition, the behavioral intentions of the elderly when experiencing VR leisure activities highlight enjoyment as the major aspect, indicating that when the elderly find an activity that is interesting and relaxing, it helps to improve health [29,30].…”
Section: Social Service Provided By Vr Technologymentioning
confidence: 99%